Solitary But Not Alone: Materialising Boundaries at a Distance with a Leafcutter Bee’s Nest - Amalie Strange (Australian Journal of Environmental Education)
More-than-human refusal, as an expression of agency, plays an active role in constructing boundaries. In this article, I address what kind of environmental education is made possible by the productive constraints of respecting more-than-human boundaries and refusal. This is intertwined with how humans can practice being attentive to the intra-actions of more-than-humans when they are not physically present, are only speculated to be present or are present through artifacts. I rhizomatically analyse my relationship with a leafcutter bee (Megachile spp.) nest as a situated example of practicing a relational ethic of care. Through queering the boundary between myself and the leafcutter bee, nature becomes not something that I (human) experience, but as something we (bougainvillea-leafcutter bee-nest-human assemblage) produce through our human-and-more-than-human relationality. Rather than seeing limited proximity as prohibitive, environmental education can use this productive constraint to know-with more-than-human others in a way that disrupts the nature/culture binary — to blur the boundaries between humans and more-than-humans without violating the agency asserted by more-than-humans.